Antiproliferative Effects of Oxytocin and Desmopressin on Canine Mammary Cancer Cells - Benavente, Micaela Andrea; Bianchi, Carolina Paula; Imperiale, Fernanda; Aba, Marcelo Alfredo (Frontiers in Veterinary Science, 2016)
Abstract Neoplasms of the mammary gland represent the most frequent tumor type in the female dog, and according to the histologic criteria, approximately 50% of them are malignant. In the most aggressive cases of mammary cancer, surgery is not enough to warrant a favorable outcome, and adjuvant therapies are needed to improve the patient’s overall survival. The aim of the present study was to evaluate the effects of two peptides on proliferation of a canine mammary cancer cell line derived from a simple carcinoma. The cell line CMT-U27 was grown in 96-well plates, at two cell densities (4 x 103 and 8 x 103 cells/well). Cultures were treated with oxytocin or desmopressin at five concentrations (10, 50, 100, 500 and 1000 nM). After 72 h of incubation, cell proliferation was determined by the MTT assay. Results showed that with 4 x 103 cells/well, oxytocin at 50, 500 and 1000 nM was growth inhibitory for the cells, being statistically significant at 1000 nM. On the contrary, no antiproliferative effect was observed with 10 or 100 nM. At 8 x 103 cells/well, oxytocin showed a significant antiproliferative effect only with the highest concentration (1000 nM). Desmopressin at 4 x 103 cells/well decreased cell viability at concentrations of 50, 100, 500 and 1000 nM (statistically significant with the highest concentration), while no effect was observed with 10 nM. With 8 x 103cells/well, this peptide reduced cell growth at 100, 500 and 1000 nM. In conclusion, we suggest that these peptides may be potential and promising compounds for the treatment of dogs with simple carcinomas of the mammary gland. In vivo studies are required to confirm this hypothesis.